2018
DOI: 10.1159/000494973
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Acute Diverticulitis: When to Operate?

Abstract: Objective: Recurrent acute diverticulitis carries a major burden to any form of health care. Patients present repeatedly to medical centers with a multitude of symptoms and may require different modalities of treatment with significant morbidities and impact on quality of life. Methods: We therefore wanted to identify factors that would imply the need and time of surgery versus conservative management. The literature was thoroughly searched for major studies tackling this topic. Furthermore, studies reporting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Researchers have previously reported that IBS increases the risk of recurrence of diverticulitis [25]. In another investigation, younger age and persistence of postoperative symptoms after resection for diverticular disease are significantly associated with recurrent diverticulitis [26,27]. However, in our study, the diagnosis of IBS was made before the first episode of AD, which means there is no possibility of mixing IBS and postoperative symptoms.…”
Section: Discussionmentioning
confidence: 62%
“…Researchers have previously reported that IBS increases the risk of recurrence of diverticulitis [25]. In another investigation, younger age and persistence of postoperative symptoms after resection for diverticular disease are significantly associated with recurrent diverticulitis [26,27]. However, in our study, the diagnosis of IBS was made before the first episode of AD, which means there is no possibility of mixing IBS and postoperative symptoms.…”
Section: Discussionmentioning
confidence: 62%
“…This patient’s presentation with recurrent diverticulitis has many atypical features including the recurrence and the complicated nature of the first presentation of diverticulitis. Though recurrent episodes of acute diverticulitis are seen in 20-35% of patients, a study examining 672 patients showed that less than 4% developed complicated diverticular disease with fistula, abscess, or frank perforation [ 3 ]. Within a span of nine months, our patient was admitted on at least five occasions with complicated diverticulitis, including a sealed perforation, colocutaneous fistula, and multiple abscesses.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis is made with a combination of clinical findings and imaging. Imaging evaluates for complications such as fistula, abscess, bowel obstruction, or perforation [ 3 ]. According to the American College of Gastroenterology (ACG), antibiotics should be selectively used in acute, uncomplicated diverticulitis but withheld in mild cases.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment ranges from observation for diverticula-associated abdominal pain to colectomy for recurrent diverticulitis [15]. Al Harakeh et al found that pancolonic diverticulosis is associated with a medium risk of recurrent diverticulitis [16]. This finding suggests that the pathogenesis of recurrent diverticulitis is multifactorial and not solely dependent on diverticula quantity.…”
Section: Discussionmentioning
confidence: 99%